OBSTACLES FOR INVESTIGATORS IN THE INVESTIGATION OF CHILD ABUSE CRIMES AT THE CIREBON POLICE - Salsabila, Aisha; Alfian, Desta Dwi; Fuadi, Shofil; Suyudi, Rasyiq; Nugraha, Farhan Haban; Khalisha, Salma Nur; Zulkifli, Mufid; Paulo, São (Ann Publisher, 2025)
Abstract: Background. Children who are victims of sexual violence are at risk of mental disorders, difficulties in social interactions, and the tendency to become perpetrators of abuse in the future. Children are vulnerable to crime no matter where they are, as abuse can also occur in a variety of environments, including family environments, educational institutions, offices, public places, or even the safest places, such as Islamic boarding schools Aims. The purpose of this research is to determine the challenges associated with providing legal protection for children who commit sexual assault at Polresta Cirebon while the investigation is ongoing. This normative legal study aims to make choices and settle disputes. Methods. Two methods of gathering data are researching the literature and conducting interviews. The data is analyzed using qualitative data analysis. Result. According to the study's findings, child investigators continue to encounter several challenges when implementing legal protection for children who engage in sexual abuse, including a shortage of child investigators, a lack of supporting documentation, and the absence of a safe house at Polresta Cirebon for investigative purposes. Conclusion. As a solution, this study recommends increasing the number of investigators trained to handle cases of violence against children, the construction of special facilities such as safe houses, and advanced training for investigators in handling child abuse cases professionally. Implementation. Thus, success in handling the crime of child abuse depends not only on existing regulations but also on the readiness of human resources, the availability of supporting facilities, and the ability of law enforcement officials to respond to each case quickly, appropriately, and favorably for the victim. Efforts to increase the capacity of investigators and construct supporting facilities such as safe houses are strategic steps in realizing a more effective and equitable child protection system.